Enterprise finance and economic development : a study of the fishing industry in Uganda and the Gambia / Seeku A. K. Jaabi - Jaabi, Seeku A. K. (2014)
Small and Medium-sized Enterprises‟ (SMEs) financing has attracted much attention in the past decades. However, most works on SMEs are focused on industrial and service sector firms. The importance of fish-based SMEs in the economic development cannot be over-emphasized as countries, such as; Uganda and The Gambia rely on these firms to support a significant segment of their populations. Over 700,000 and 200,000 people respectively in Uganda and The Gambia depended on fish for their livelihood in 2006. Despite its importance, fish operatives in both countries continue to face problems of lack of technology and access to finance. Hence, this study examines institutional and supply-side constraints facing fish production, and the relationship between technology and exports, and between access to finance and R&D, and exports in Uganda and The Gambia. The thesis is organized into seven chapters. After the introduction, chapter discusses the theoretical considerations. Chapters three, four, five and six analyze comparatively four important relationships respectively, namely, importance of fishery industry, institutional and technological constraints facing the industry, problems affecting access to finance, and variables affecting operative performance. Chapter seven presents the conclusions. The evidence shows that institutional and supply-side constraints have affected production capabilities in the two countries differently. Although capabilities in Uganda and The Gambia have not reached the technology frontier, the EU ban on fish imports into Europe triggered an institutional response that led to technological capability building to address sanitary problems facing the industry. The improved physical and knowledge infrastructure, which has enabled technological adaptation in the fish processing chain, coupled with a stable and enabling macroeconomic environment has helped propel fish exports to iv sophisticated markets in the West. The lack of it has restricted fish exports from The Gambia. In addition, the evidence shows that size and age matter in fish SMEs‟ ability to access finance. The lack of collateral, which is a chronic problem associated with small firms, is the primary constraint facing SMEs‟ inability to access finance. Uganda and The Gambia are no different from other developing countries as size is often the prime constraint that restricts financial access. Furthermore, access to finance and R&D have a strong relationship with export performance and value added. Operatives with greater access to finance and R&D incidences show strong export performance. These results support the general theory of financial access and R&D. Hence, it is clear that both financial and technological capabilities are important for the fish operatives to compete in global markets. Taken together, the evidence shows that institutional support is critical to provide the systemic pillars essential to stimulate fish exports from The Gambia and Uganda, which is very much consistent with the evolutionary arguments. Governments should then strife to strengthen the systemic pillars of basic infrastructure, high tech infrastructure, global integration and network cohesion to support technological upgrading. The evidence also shows that size and age matter in access to external finance. Hence, SMEs‟ access to financial access problems can be reduced through special policies to underwrite the need for collateral. Furthermore, financial access and R&D are important in stimulating fish exports in both countries. Hence, even in LDCs, the Schumpeterian argument of innovation is essential to support competitiveness in export markets. The governments of Uganda and The Gambia should focus on supporting fish operatives with essential finance to undertake R&D so as to stimulate further fish exports.